Targeting epigenetics as atherosclerosis treatment: an updated view. Issue 6 (December 2020) - Neele, Annette E.; Willemsen, Lisa; Chen, Hung-Jen; Dzobo, Kim E.; de Winther, Menno P.J.
Abstract : Purpose of review: This review discusses the current developments on epigenetic inhibition as treatment for atherosclerosis. Recent findings: The first phase III clinical trial targeting epigenetics in cardiovascular disease (CVD), BETonMACE, using the bromodomain inhibitor apabetalone (RVX-208) showed no significant effect on major adverse cardiovascular events (MACE) in patients with type II diabetes, low HDL-c and a recent acute coronary artery event compared with its placebo arm. Summary: Preclinical and clinical studies suggest that targeting epigenetics in atherosclerosis is a promising novel therapeutic strategy against CVD. Interfering with histone acetylation by targeting histone deacetylates (HDACs) and bromodomain and extraterminal domain (BET) proteins demonstrated encouraging results in modulating disease progression in model systems. Although the first phase III clinical trial targeting BET in CVD showed no effect on MACE, we suggest that there is sufficient potential for future clinical usage based on the outcomes in specific subgroups and the fact that the study was slightly underpowered. Lastly, we propose that there is future window for targeting repressive histone modifications in atherosclerosis.